The Roles of Digital Transformation for MSME's Growth - Fauziana, Eva; Rizkia Budi, Yeniasari (Adpebi International Journal of Multidisciplinary Sciences, 2023)
This research is to find out the influences of digital transformation to the MSME’s development and growth, especially after COVID 19. This research would like to gain what the digital media mostly used by the MSME owners and whether the owners got the positive impacts after using them, and whether the positive impacts including the significant profit for their business. This research is also to find out how they learnt the digital media and who coach them to use the tools. This research is using quantitative methods, spreading the questionnaires to 230 respondents and having 72 valid responses to be analyzed.